2016
DOI: 10.1093/arclin/acv090
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Everyday Functioning in the Internet Age: HIV-Associated Neurocognitive Disorders Disrupt Online Pharmacy and Health Chart Navigation Skills

Abstract: This study evaluated the effects of HIV-associated Neurocognitive Disorders (HAND) on 2 Internet-based tests of healthcare management. Study participants included 46 individuals with HIV infection, 19 of whom were diagnosed with HAND, and 21 seronegatives. Participants were administered Internet-based tests of online pharmacy and health records navigation skills in which they used mock credentials to log in to an experimenter-controlled website and independently perform a series of typical online health-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
77
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(88 citation statements)
references
References 30 publications
10
77
0
1
Order By: Relevance
“…Although one RCT scored 8 of 13 [23] and one of three quasi-experimental studies scored 6 of 9, [24] they had strengthened validity of causal inferences by comparing control and intervention groups. In addition, two quasi-experimental studies scored 6 of 9 [25,26] and lacked a comparison group to determine pre-post intervention effects.…”
Section: Characterizing the Evidence Basementioning
confidence: 99%
See 4 more Smart Citations
“…Although one RCT scored 8 of 13 [23] and one of three quasi-experimental studies scored 6 of 9, [24] they had strengthened validity of causal inferences by comparing control and intervention groups. In addition, two quasi-experimental studies scored 6 of 9 [25,26] and lacked a comparison group to determine pre-post intervention effects.…”
Section: Characterizing the Evidence Basementioning
confidence: 99%
“…Four studies were conducted in the U.S., [24][25][26][27] two in Uganda, [23,28] and one in Peru. [29] Various study designs were used: cross-sectional, [27][28][29] quasi-experimental, [24][25][26] and a RCT. [23] Two studies identified a theoretical or conceptual framework used in their research.…”
Section: Overview Of Studies Included In the Reviewmentioning
confidence: 99%
See 3 more Smart Citations